Kidney Disease Profile of Syrian Refugee Children (Iranian Journal of Kidney Diseases, 2017)
Introduction. Although preventative nephrology is the effective management of childhood kidney diseases, it is hard to provide it in this undesirable conditions. In this study, we aimed to document the kidney disease profile of Syrian refugee children admitted to our hospital. Materials and Methods. One hundred and thirty Syrian refugee children were admitted to the Pediatric Nephrology Department of the University of Gaziantep from September 2012 to January 2015. Demographic data, history, symptoms, physical examination findings, laboratory investigations, diagnosis, disease outcome, and therapeutic procedures such as peritoneal dialysis and hemodialysis were obtained from patient files. Results. Of the 130 admitted children, 74 were girls (59.6%). The average age was 6.97 ± 4.2 years (range, 1 month to 17 years). Congenital abnormalities of the kidney and urinary tract were found in 34 children (26.2%). Other morbidities were chronic kidney disease in 30 (23.1%), nephrotic syndrome in 24 (18.5%), urolithiasis in 9 (6.9%), acute kidney injury in 4 (3.1%), glomerulonephritis in 5 (3.8%), enuresis in 12 (9.2%), and others in 12 (9.2%). Conclusions. Congenital abnormalities of the kidney and urinary tract and chronic kidney disease were highly prevalent in Syrian refugee children. Although free health care have been provided to all of these children, the continuation of political crisis and instability would increase the number of admissions and affect the quality of life of those children in a different environment from the home country.